Plasticity of Innate Lymphoid Cells in Cancer - Heinrich, Bernd; Korangy, Firouzeh (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) are a heterogenous population of the innate immune system, enriched at mucosal surfaces and are pivotal regulators of immune homeostasis. ILCs are the innate counterpart of T cells. Like T cells, ILC subsets are highly plastic with their composition and function controlled by alterations in their microenvironment. This plasticity allows for the trans-differentiation between the subsets to rapidly respond to their immune environment. The tumor microenvironment (TME) is a heterogeneous milieu characterized by different cytokines and growth factors. Through interaction with the tumor microenvironment, ILCs can transdifferentiate into different subsets resulting in pro or anti-tumor immunity. Thus, studying ILC plasticity might result in new therapeutic approaches for cancer therapy. In this review, we summarize current findings of the functional and plastic heterogeneity of ILCs in homeostasis as well as disease settings with a specific focus on cancer. We specifically highlight tumor-driven plasticity and how ILC-induced inflammation can impact the tumor microenvironment and anti-tumor immunity.